Prostate cancer theranostics with 177Lu-PSMA - Ahmadzadehfar, Hojjat; Seifert, Robert; Afshar-Oromieh, Ali; Kratochwil, Clemens; Rahbar, Kambiz (Seminars in nuclear medicine, 2024)
This review paper highlights the transformative role of PSMA-targeted diagnostics and therapy in prostate cancer management, particularly focusing on 177Lu-PSMA-617, approved by the FDA and EMA for metastatic castration-resistant prostate cancer (mCRPC) patients post-chemotherapy and ARPI treatment. Originating from the VISION trial's success, this paper navigates the current radioligand therapy (RLT) indications, emphasizing practical patient selection, planning, and treatment execution. It critically examines Lu-PSMA's comparative effectiveness against cabazitaxel and Ra-223, addressing decision-making dilemmas for mCRPC treatments. Furthermore, the paper discusses Lu-PSMA in chemotherapy-naïve patients and its application in hormone-sensitive prostate cancer, underlined by ongoing global studies. A significant concern is Lu-PSMA's long-term safety profile, particularly nephrotoxicity risks, necessitating further investigation. The possibility of Lu-PSMA rechallenge in responsive patients is explored, stressing the need for comprehensive analyses and real-world data to refine treatment protocols. Conclusively, PSMA-targeted therapy marks a significant advance in prostate cancer therapy, advocating for its integration into a multimodal, patient-centric treatment approach. The review underscores the imperative for additional comparative studies to optimize treatment sequences and outcomes, ultimately enhancing long-term prognosis and disease control in prostate cancer management.